On Î¸-Totally Disconnected and Î¸-Light Mappings - Jebur Ali, Haider; Fadel Abass, Huda (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
In our research, we introduced new concepts, namely *and **-light mappings, after we knew *and **-totally disconnected mappings through the use of -open sets. Many examples, facts, relationships and results have been given to support our work.